Cutaneous horn - Fernandes, Neil F. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2009)
A cutaneous horn is a conical, dense, hyperkeratotic protrusion that often appears similar to the horn of an animal. It is a morphologic designation referring to an unusually cohesive keratinized material, not a true pathologicdiagnosis. Cutaneous horns occur in association with, or as a response to, a wide variety of underlying benign, pre-malignant, and malignantcutaneous diseases. The most important common concern is distinguishing a hyperkeratotic actinic keratosis from a cutaneous squamous cell carcinoma. Keratoacanthoma is another cause, as illustrated herein as a projective cutaneous tumor with a fingernail-like appearance. The treatment ofchoice for cutaneous horns is shave excision with subsequent histopathologic evaluation to rule out underlying malignancy and to guide potential further therapy.
Keywords: dermatologija; Diagnosis; diagnostika; histopatologija; Keratoacanthoma; Keratoakantom; Keratosis; Keratoza; keratoze; Pathology